2021
DOI: 10.1099/jgv.0.001687
|View full text |Cite
|
Sign up to set email alerts
|

Simulated vector transmission differentially influences dynamics of two viral variants of deformed wing virus in honey bees (Apis mellifera)

Abstract: Understanding how vectors alter the interactions between viruses and their hosts is a fundamental question in virology and disease ecology. In honey bees, transmission of deformed wing virus (DWV) by parasitic Varroa mites has been associated with elevated disease and host mortality, and Varroa transmission has been hypothesized to lead to increased viral titres or select for more virulent variants. Here, we mimicked Varroa transmission by serially passaging a mixed population of two DWV variants, A and B, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 84 publications
5
28
1
Order By: Relevance
“…Conversely, PBS injection and mite exposure pupal treatment groups induced higher levels of DWV-B but not DWV-A (Figure 2). The elevated levels of DWV-B in the PBS and mite treatment groups are also similar to prior responses seen in adult bees but not necessarily in pupae (Wu et al, 2017;Dubois et al, 2020;Norton et al, 2020;Penn et al, 2021;Ray et al, 2021). The differential responses to viral infection between pupae and adults have been previously documented both in infection levels and in the ability of dsRNA treatments to mitigate infections (Möckel et al, 2011;Desai et al, 2012;Thaduri et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Conversely, PBS injection and mite exposure pupal treatment groups induced higher levels of DWV-B but not DWV-A (Figure 2). The elevated levels of DWV-B in the PBS and mite treatment groups are also similar to prior responses seen in adult bees but not necessarily in pupae (Wu et al, 2017;Dubois et al, 2020;Norton et al, 2020;Penn et al, 2021;Ray et al, 2021). The differential responses to viral infection between pupae and adults have been previously documented both in infection levels and in the ability of dsRNA treatments to mitigate infections (Möckel et al, 2011;Desai et al, 2012;Thaduri et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Several experimental studies in which honey bee adults and pupae have been inoculated with DWV-A or DWV-B show that DWV-B replicates faster that DWV-A (e.g. McMahon et al, 2016 ; Tehel et al, 2019 ; Norton et al, 2020 ), at least during its first experimental passage through a host pupa ( Ray et al, 2021 ). High titres are generally – though not always – associated with greater pathogen transmission ( Schmid-Hempel, 2011 ), which provides the basis for our initial estimate of μ (the colony-level rate of transmission) to lie at 0.1 and 0.15 for DWV-A and DWV-B, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Though a DWV-A/B recombinant with higher virulence than DWV-A was found to predominate in British honey bees in the Warwick-HRI apiary ( Moore et al, 2011 ; Ryabov et al, 2014 ), recombinants have been found to be surprisingly infrequent in more recent analyses of the continental US honey bee population ( Ryabov et al, 2017 ). Furthermore, experimental co-infection of honey bees with DWV-A and a putative DWV-A/B recombinant and passaging through honey bee pupae did not appear to lead to novel recombinants, though the original A/B recombinant was stable over repeated passages ( Ray et al, 2021 ). Finally, Gusachenko et al (2021) found that recombinant DWV did not out-replicate parental variants in laboratory assays (reviewed in Woodford and Evans, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the major variants, DWV variant B (DWV-B) is more prevalent in Europe, whereas DWV variant A (DWV-A) is widespread in North America [32,[38][39][40][41]. On several occasions, DWV-B has been shown to outcompete DWV-A in laboratory experiments and field surveys [41][42][43][44][45], although the results seem to depend on the methodology followed in the study [46]. The rapid spread of DWV-B in Hawaii following the recent mite invasion also suggests a strong selective advantage of this variant over DWV-A when the parasite is present [28,45].…”
Section: Introductionmentioning
confidence: 99%